Role of Rapid Drink Challenge During Esophageal High-resolution Manometry in Predicting Outcome of Peroral Endoscopic Myotomy in Patients With Achalasia - Foisy, Hélène (J Neurogastroenterol Motil, 2020)
BACKGROUND/AIMS: Peroral endoscopy myotomy (POEM) is effective to treat achalasia. We aim to determine POEM effect on esophageal function and search for predictive factors of response to POEM and co-occurrence of gastroesophageal reflux disease (GERD). METHODS: A total of 64 untreated achalasia patients who underwent high-resolution manometry (HRM) before and 3 months after POEM were retrospectively included. Response to treatment was defined as an Eckardt score < 3. Reflux symptoms and patient's satisfaction were evaluated. Data were compared using paired t test, Chi-square test or log rank test. RESULTS: The 2-year success rate in response to POEM was 90%. All responders reported being satisfied while only 33% of non-responders did (P < 0.001) and 64% of patients with reflux symptoms were satisfied versus 96% of those without (P = 0.009). On HRM, the integrated relaxation pressure and the contractile pattern changed significantly after POEM but were not predictive of response. Between pre and post POEM HRM, a decrease in maximal esophageal pressurization during rapid drink challenge (RDC) was associated with a better response rate than an increase of pressurization (91% vs 50%, P = 0.004). As evidenced by pH monitoring performed after POEM, GERD was pathological or borderline in 50% of patients (18/36) while only 19% (11/59) reported clinically significant reflux symptoms. On post POEM HRM, maximal esophageal pressurization during RDC was lower in patients with pathological or borderline GERD compared to those without (P = 0.054). CONCLUSIONS: Esophageal HRM parameters changed significantly after POEM. Maximal esophageal pressurization during RDC may be useful to predict outcome.